Pengaruh Digital Leadership, Literasi Teknologi, Dan Fasilitas Digital Terhadap Kinerja Pengajaran Guru Di Sekolah Dasar Rabbaanii Islamic School - Prasetyo, Hari; Fathorrahman, Fathorrahman; Murtianingsih, Murtianingsih (Publikasi Indonesia, 2025)
This study aims to analyze the influence of digital leadership, technological literacy, and digital facilities on teaching performance of teachers at Rabbaanii Islamic Elementary School. The research uses a quantitative approach with multiple linear regression analysis techniques. The research sample consisted of 40 teachers using saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using SPSS. The results show that simultaneously, digital leadership, technological literacy, and digital facilities have a significant effect on teacher teaching performance with a contribution of 51.7%. Partially, only technological literacy proved to have a significant effect on teacher teaching performance (sig. 0.000 < 0.05), while digital leadership (sig. 0.214 > 0.05) and digital facilities (sig. 0.088 > 0.05) did not have a significant effect. These findings indicate that teachers' readiness and ability to use technology plays an important role in improving the quality of teaching processes. The research provides implications for school administrators to strengthen digital literacy programs for teachers and improve more participatory digital leadership strategies as well as optimize the utilization of digital facilities.